PENGUNGKAPAN LAPORAN KEUANGAN PADA PEMERINTAH DAERAH DI INDONESIA: Telaah Faktor-Faktor Potensial - Alif Suci Miranti (2020)
The purpose of this study is to study the factors that drive the level of disclosure in local government financial reports including the human development index, liabilities, local own-source revenue, general allocation funds, and legislator size. The sample used in this study was 137 financial statements of district / city governments in Kalimantan and Sulawesi in 2018. Technical analysis used was multiple linear regression analysis. The results showed that: 1) the human development index had no effect on disclosure 2) liabilities had no effect on disclosure 3) original regional income had no effect on disclosure 4) general allocation funds had a significant positive effect on disclosure and 5) legislator size had no effect towards disclosure